2022
DOI: 10.1002/pssr.202100624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Physical Properties of BaSnS2

Abstract: Phase‐pure BaSnS2, with space group P21/c, is synthesized, and the structural and physical properties are investigated. Thermal properties and optical measurements are reported for the first time. The Debye temperature and Sommerfeld coefficient are obtained from temperature‐dependent heat capacity measurements, the latter indicating that BaSnS2 is an electrical insulator. A direct bandgap of 2.4 eV is obtained from diffuse reflectance and photoluminescence spectroscopy. The findings herein lay the foundation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…E d G decreases from 2.25 eV in BaS to 1.59 eV in SnS ( Pnma ), but jumps to 2.07 eV in the SnS ( Aem 2) polymorph. Previous studies have reported BaSnS 2 HSE gap of 2.4 eV, 43 BaSnS 2 experimental gap of 2.4 eV, 12 BaSnS 3 HSE gap of 2.62 eV; 44 each of these are similar to our reported values. To our knowledge, this is the first HSE gap report for BaSn 2 S 3 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…E d G decreases from 2.25 eV in BaS to 1.59 eV in SnS ( Pnma ), but jumps to 2.07 eV in the SnS ( Aem 2) polymorph. Previous studies have reported BaSnS 2 HSE gap of 2.4 eV, 43 BaSnS 2 experimental gap of 2.4 eV, 12 BaSnS 3 HSE gap of 2.62 eV; 44 each of these are similar to our reported values. To our knowledge, this is the first HSE gap report for BaSn 2 S 3 .…”
Section: Resultssupporting
confidence: 92%
“…5 The rst Ba-Sn-S compound, a perovskite phase of BaSnS 3 (Pnma), was synthesized in 1970 using a high-pressure bulk synthesis method. 6 Several more bulk crystalline phases have been grown since, including Ba 3 Sn 2 S 7 (P2 1 /c), 7,8 Ba 2 SnS 4 (Pna2 1 ), 9,10 BaSnS 2 (P2 1 /c), 11,12 and BaSn 2 S 3 (P12 1 /m). 13 In the 2010s Ba-Sn-S was studied for nonlinear optics applications, yielding compounds with more complicated stoichiometries and structures: Ba 6 Sn 7 S 20 (C2/c), Ba 7 Sn 5 S 15 (P6 3 cm), BaSn 2 S 5 (Pccn), Ba 8 Sn 4 S 15 (Pca2 1 ), Ba 7 Sn 3 S 13 (Pnma), and Ba 12 Sn 4 S 23 (P2 1 c).…”
Section: Introductionmentioning
confidence: 99%
“…The width of fundamental band gap of pure BaSnS 2 in our calculation is 2.31 eV, which is consistent with the experimental result of 2.40 eV. 44 Although BaSnS 2 is a semiconductor with a ‘quasi-direct’ band gap, some theoretical studies suggested that indirect band gap semiconductors with small energy difference can be regarded as promising photovoltaic absorbers. 59,60 Therefore, BaSnS 2 with ‘quasi-direct’ band gap can also be employed as the host of absorber for IBSC.…”
Section: Resultssupporting
confidence: 90%
“…14) and the calculated crystal parameters are a = 6.07 Å, b = 11.51 Å, and c = 6.05 Å, respectively, which agree well with the experimental results ( a = 6.09 Å, b = 12.16 Å, and c = 6.24 Å). 44 The unit cell with 16 atoms and 2 × 1 × 1 supercell with 32 atoms containing one dopant atom were utilized to consider two different doping concentrations of 25% and 12.5%, respectively. For K -points sampling, the Γ -centered grid 48 of 5 × 3 × 5 was employed for the calculations on structure relaxation, electronic structures and optical properties of pure BaSnS 2 .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation